Long-term detection and hydrochemistry of groundwater resources in Egypt: Case study of Siwa Oasis - Anwar A. Aly; Fawzy M. Kishk; Hesham M. Gaber; Abdulrasoul M. Al-Omran (Journal of the Saudi Society of Agricultural Sciences, 2016)
Water, it is said, will be the oil of the twenty-first century. Successful water management will be the key to future economic growth and social wealth in both developed and developing countries. Due to the continuous agricultural expansion, urban development, and increased demands on limited water supplies, Egypt is compelled to look for unconventional water resources. One of the most important sources is groundwater in the western desert of Egypt. More water abstraction is currently taking place raising the dangers of overexploitation and deterioration of water quality in Siwa Oasis located in Egypt western desert. The main objectives of this study are to monitor the quality of the Siwa Oasis groundwater over ten years. The present paper presents the results of this investigation and the future outlook for the situation of the limited water resources of the oasis. The data showed spatial differences between water qualities obtained from different locations within the Oasis. It was also observed that there are temporal changes and that water quality is deteriorating in alarming rate over time. Most studied water samples were considered unsuitable for irrigation due to salinity hazards. The reason that may contribute to speeding up groundwater quality deterioration is the unsafe ground water mining on the deep sandstone aquifers which causes the decreases of the fresh water vertical movement from the deep sandstone aquifer to the surface limestone aquifer.